Feminist Movement In Indian Literary Works: Exploring the feminist movement and gender equality in Indian literature (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The feminist movement, "includes any form ofopposition to any form of social, personal or economic discrimination whichwomen suffer because of their sex."(2), so says David Bouchier in the"Introduction" to his book The Feminist Challenge. The desirefor equality with men on the social and political fronts took the form of anorganised movement in the west. It includes both the struggle for women's equalrights as well as the aspirations and strivings towards the all roundliberation of women, which is considered as emancipation.